PREPARATION AND EVALUATION OF DIACEREIN LOADED MICROSPHERE WITH SODIUM ALGINATE AND ETHYL CELLULOSE BY DOUBLE EMULSION SOLVENT EVAPORATION METHOD - SOUMEN MUKHOPADHYAY; SHARMILY CHAKRABORTY; SUMANTA DAS; Dr.TAPAN KUMAR CHATTERJEE (International Journal of Pharma and Bio Sciences, 2016)
The present study was conducted to prepare microsphere of poorly water soluble drug Diacerein by double emulsion method (W/O/W) where sodium alginate was used as drug release retarding polymer in microsphere formulation and ethyl cellulose was used as coating polymer. Diacerein was found to be compatible with matrix polymer and co-polymer by conducting the various physicochemical and instrumental analyses. Three different Diacerein loaded microspheric formulations were prepared using variable concentrations of Sodium alginate and Ethyl cellulose as it was found that entrapment efficiency and particle size of the microspheres were increased on increasing polymer concentration of formulations and on increasing polymer concentration the drug release of all the formulations were gradually decreased.Though not being categorized as anonsteroidal anti-inflammatory drug, Diacerein has significant role in pain therapy. It can be concluded that preparing Diacerein microsphere using sodium alginate and ethyl cellulose polymers can be a new addition in the field of pain management as sustained release therapy.